1955
DOI: 10.1002/cber.19550881106
|View full text |Cite
|
Sign up to set email alerts
|

Notiz über einige Derivate der Thiodiglykolsäure

Abstract: Durch Umsetzung von Chloressigsäure‐Derivaten mit Natriumsulfid werden einige Thiodiglykolsäure‐Abkömmlinge dargestellt. Ihre UV‐Spektren werden mitgeteilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…From this data, it could be observed that the Lyocell fibers exhibiting higher LOI have a lesser fibrillability. Schurz discussed the lateral clusters of cellulose chains in terms of crystalline orientation-physical property relationship in Lyocell fibers and their importance in determining the fibrillation behavior [43]. Furthermore, comparison of Figure 7(b) with (c) has already revealed that the fibrillation is dependent on molecular weight and dope concentrations.…”
Section: Fibrillation Behavior Of Cotton Linter Based Regenerated Celmentioning
confidence: 98%
“…From this data, it could be observed that the Lyocell fibers exhibiting higher LOI have a lesser fibrillability. Schurz discussed the lateral clusters of cellulose chains in terms of crystalline orientation-physical property relationship in Lyocell fibers and their importance in determining the fibrillation behavior [43]. Furthermore, comparison of Figure 7(b) with (c) has already revealed that the fibrillation is dependent on molecular weight and dope concentrations.…”
Section: Fibrillation Behavior Of Cotton Linter Based Regenerated Celmentioning
confidence: 98%